2016
DOI: 10.1177/1524838016669508
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Intimate Partner Violence With Latina Women: A Call for Research

Abstract: Latina women, especially those who are immigrants, have an increased vulnerability to intimate partner violence, yet they also have a low rate of using formal services (i.e. health care and legal services). Existing research focused on Latina women's help seeking for intimate partner violence has identified multiple factors, such as the presence of children, cultural values, and type of victimization, that influence women's formal help seeking. Immigrant Latina women in particular commonly report many barriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 48 publications
2
65
0
Order By: Relevance
“…Among our participants, it was not clear whether those who did not seek support felt there was inadequate support (i.e., accessibility, sociallyand culturally-appropriate) from social services, the police, or their church, or whether they did not seek help that was actually available for other reasons. Researches (10,27) suggest that immigrants might be less likely to seek help for IPV because of many post-migration factors: lack of social supports, socioeconomic status of women in their home country, or lack of financial resources (of the victim or her partner). The presence of children, the type of victimization, and cultural values also influence women to seek help (27) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among our participants, it was not clear whether those who did not seek support felt there was inadequate support (i.e., accessibility, sociallyand culturally-appropriate) from social services, the police, or their church, or whether they did not seek help that was actually available for other reasons. Researches (10,27) suggest that immigrants might be less likely to seek help for IPV because of many post-migration factors: lack of social supports, socioeconomic status of women in their home country, or lack of financial resources (of the victim or her partner). The presence of children, the type of victimization, and cultural values also influence women to seek help (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Researches (10,27) suggest that immigrants might be less likely to seek help for IPV because of many post-migration factors: lack of social supports, socioeconomic status of women in their home country, or lack of financial resources (of the victim or her partner). The presence of children, the type of victimization, and cultural values also influence women to seek help (27) . A scoping review conducted with data from 2000 to 2015 concluded that there is a low level of education for nursing/midwifery staff and students, so many nurses lack knowledge and skills in identifying, understanding, and providing appropriate care for women living with IPV (28) .…”
Section: Discussionmentioning
confidence: 99%
“…12 The US Latino population reached nearly 60 million in 2018, 13 16 Violence against Latinas has been reported as a main cause of morbidity, injury, and death. 17 Among Latinas under the age of 44, unintentional injuries is the top cause of mortality. 16 The sexual health needs of Latinas include access to comprehensive sexuality education as well as gynecological care.…”
Section: Latinas' Healthmentioning
confidence: 99%
“…IPV refers to physical, sexual, and/or psychological violence experienced by a current or former intimate partner (Breiding et al 2015) and is a public health epidemic affecting individuals across socioeconomic status, national origin, ethnicity, gender expression, and sexual orientation. While women of various ethnic and racial backgrounds experience IPV at approximately the same rate once socioeconomic factors are accounted for (Cho 2012;Zadnik et al 2016), research suggests that Latinas experience disparate outcomes following IPV (Alvarez and Fedock 2018). In recent years scholars have begun to examine IPV within distinct groups of racial and ethnic minority women (Gillum 2008).…”
Section: Introductionmentioning
confidence: 99%